2014
DOI: 10.1016/j.rgg.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of the sapropel sediments of small lakes in the Ob’–Irtysh interfluve

Abstract: More than 20,000 lakes with sapropel sediments are located in southern West Siberia. The work is aimed at an integrated geochemical study of ten sapropel lake systems: a geochemical description of the lake waters, hydrobiological analysis, and analysis of the sapropels (phase and chemical analyses of inorganic matter and elemental analysis of organic matter). The geochemical landscape and low-flow regime of the waters of Siberian small lakes favor massive growth of living organisms. The anaerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…The occurrence and development of small lakes is directly related to the formation of terrain and changes in natural and climatic conditions. The study of sedimentation processes in small lakes has shown that there is a certain set of factors that affects the sediment's geochemical composition [3][4][5][6][7][8][9][10]. The hallmark of each lake is the composition of the water, bedrock, and soil of the catchment area, the sediments and biota, and the life processes which occur both in the lake itself and the corresponding coastal zone.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence and development of small lakes is directly related to the formation of terrain and changes in natural and climatic conditions. The study of sedimentation processes in small lakes has shown that there is a certain set of factors that affects the sediment's geochemical composition [3][4][5][6][7][8][9][10]. The hallmark of each lake is the composition of the water, bedrock, and soil of the catchment area, the sediments and biota, and the life processes which occur both in the lake itself and the corresponding coastal zone.…”
Section: Introductionmentioning
confidence: 99%
“…Being sensitive to the increased concentration of chlorides (note: only increase in chlorides concentration up to 1 g/l brings to an increase in phytoplankton production), phytoplankton production is practically independent of mineralization. At the same time, with phytoplankton production growth, an increase in nitrogen compound concentrations occurs in water due to the rapid development of nitrogen-fixing cyanobacteria (Strakhovenko et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, fine-grained sediments can deposit alongside the organic sapropel matter, often resulting in a transition from pure sapropel to an almost organic-free mud or 'sapropel mud' (Gomes et al, 2013). Sapropel is thus a rich organic matter that has in it the remains of water organisms (phytoplankton, zooplankton, and macrophytes) and whose formation process differentiates it from its peat precursor (Strakhovenko et al, 2014;Leonova et al, 2015). Sapropel has long been used as a remedy both in veterinary and human medicine.…”
Section: Sapropelmentioning
confidence: 99%
“…Freshwater sapropel is usually found as sediments in lakes, and in some cases in marshes and bogs as well, while brackish water sapropel forms in marine reservoirs. Both types are formed by biochemical, microbiological and mechanical processes (Strakhovenko et al, 2014). Freshwater sapropel is mostly found in the territory of northern and eastern Europe.…”
Section: Sapropelmentioning
confidence: 99%